WEAR RESISTANCE OF ELECTRIC-SPARK COATINGS, OBTAINED FROM POWDER WIRE, IN CONTACT WITH WOOD - Голубець, Володимир; Пашечко, Михайло; Гончар, Іван; Шпуляр, Юрій; Гасій, Олександр (Problems of Friction and Wear, 2022)
The paper investigates the main tribological characteristics (wear values and friction coefficients) of electric-spark coating (ESC), which was applied to the working surface of the 9XC tool steel using powder wire electrodes, in contact with wood depending on the species of the wood. its moisture content and the wood grain. The ESC was applied to the tool steel after hardening and low tempering. Determined was the influence of the chemical composition of powder wires of various systems on the frictional behavior of the materials under study in the conditions of contact interaction during reciprocating motion. It was found that ESC wear in contact with wet wood is greater than in contact with dry wood. The influence of moisture on the tribological characteristics of the selected ESC system is characterized. A higher value of the coefficient of friction in contact with wet wood was recorded. Under the selected testing conditions for the friction pair «9XC steel-wood», normal mechanochemical wear was determined with the formation of secondary structures that are subject to periodic destruction and restoration. The average values of wear of friction pairs «wood- 9XC steel with ESC» obtained in the process of tribological studies indicate that the most effective for use in the technology of electrospark alloying in terms of wear resistance is the PWG electrode made from powder wire of the Fe-Cr-B-C system with graphite addition. The choice of this electrode is due to its widespread use for the restoration of worn surfaces by applying coating, low cost, a 2.5 ... 4 times better wear resistance of the welded material compared to the 9XC tool steel after hardening and low tempering, which significantly changes the engineering of the surface layer. The indexes of micro- and submicro-volumes of the surface layer of this ESC indicate high hardness, an increase in creep up to 0.97 %, relaxation ability up to 0.51 %, Young’s modulus up to 207.86 GPa, which leads to an increase in strength. The structure of ESC from PWG is an austenitic matrix with boride inclusions (Fe, Cr)B, iron boride Fe2B, and chromium iron borides Cr1.65Fe0.35B0.96.